(untitled) - The World Bank in Vietnam (WB) (Ha Noi, 2005)
The proposed project development objective would be to promote market-oriented agricultural diversification with the aim of increasing and stabilizing the incomes of poor smallholders in the central highland and coastal provinces. This would contribute to the growth of the rural economy and the reduction of rural poverty in the country’s central region. The expected specific outcomes of the proposed project would be that: (i) farmers adopt new crops and new environmentally sound production and post harvest techniques; (ii) farmers adopt new livestock production and animal heath techniques; (iii) farmers increase productive on-farm investments; (iv) farmers have increased access to information on agricultural markets, including prices; and, (v) food safety and standards are promoted for agricultural produce. As under ADP, the tarfet group for the proposed project would be poor rural households in the central highland nad coastal region engaged in agricultural activities. Particular attention would be given to the participation of the ethnic minorities and women.
Keywords: Agricultural administration.,Quản lý nông nghiệp,Animal products,Chăn nuôi